Local Solvability for the 2-coupled System of Nonlinear Schrodinger Equations in a Banach Algebra Eo2,1 (European Journal of Pure and Applied Mathematics, 2010)
This paper is concerned with initial value problem of the nonlinear coupled Â Schrodinger equations. We study local well posedness in the Banach algebra $E^0_{2,1}(R^n)$ which is the extension of $H^s(R^n)$ when Â $s\ge \frac n2.$ The method we use is similar to the method of semigroup.